Spectroscopic Based Ammonia Measurement System - Arman, Abdallah; Daghameen, Khalid; Balbisi, Eyas; Hajjaj, Muhammad (International Journal of Applied Science and Research, 2023)
This article describes the design and implementation of a microcontroller-based system for determining ammonia concentrations in blood. By adding a blood sample to a test strip, the proposed system induces a series of reactions known as Berthelot's response, resulting in an accurate change in strip color. A current is then generated when the photodiode detects the 635 nm wavelength reflected off the strip. An op-amp is used to convert the current to voltage. Because of their ease of use and software flexibility, microcontrollers are recognized as important components in modern electronics. The concentration of (NH3) is determined by a microcontroller depending on the voltage value. The test results are shown on an LCD or recorded in data files. Any normal or abnormal outcomes are appropriately recorded by the system. A PC software program is written to accept and save data. The proposed system is initially designed using the concepts of Software Analysis and Design; the process of building the proposed systems begins with determining the system's requirements, working on the analysis, using the best design techniques according to the software Engineering process, and finally modeling it on an electronic board before being realized and implemented. It is used in biomedical measurements. It is also handy for monitoring and researching final circuits
Keywords: Systems Engineering Application; Spectroscopic; Blood Ammonia; Beer-Lambert law